(untitled) (International Journal of Physiotherapy, 2015)
Background: Mechanical Low back pain is a leading cause of disability. It occurs in similar proportions in all cultures, interferes with quality of life and work performance. Both male and female populations are affected; however, there is a tendency towards a higher incidence in male patients. Mechanical low back pain is associated with pain and clinical instability in lumbar motion segments. Exercises play an important part in the rehabilitation of low back pain. The aim of this study was to compare the effectiveness between Core stabilization vs McKenzie exercises in the treatment of patients with mechanical low back pain. Methods: 30 patients were selected between the age groups of 20 yrs to 50 yrs and having a past history of low back pain for one month. 15 patients were allotted to each group of experiment. Group I was given Core stabilization exercises and Group II with McKenzie exercises. Interferential therapy was a common treatment for both the groups. Evaluations of the subjects were done using the Revised Oswestry Disability Index and Dynamic Endurance tests. Results: Data analysis revealed statistically significant difference between both the groups (p<0.05) and proved that Core stabilization exercises is more effective than McKenzie exercises in mechanical low back pain. Conclusion: This study shows that core stabilization exercises possess a greater potential over McKenzie exercises in treating Mechanical Low back pain patients.